Antioxidant Activity of Grapevine Leaf Extracts against Oxidative Stress Induced by Carbon Tetrachloride in Cerebral Cortex, Hippocampus and Cerebellum of Rats - Wohlenberg, Mariane (Antioxidants (Basel), 2014)
In recent years, it has become increasingly important to study the beneficial properties of derivatives of grapes and grapevine. The objective of this study was to determine the antioxidant activity of Vitis labrusca leaf extracts, comparing conventional and organic grapevines, in different brain areas of rats. We used male Wistar rats treated with grapevine leaf extracts for a period of 14 days, and on the 15th day, we administered in half of the rats, mineral oil and the other half, carbon tetrachloride (CCl(4)). The animals were euthanized by decapitation and the cerebral cortex, hippocampus and cerebellum were removed to assess oxidative stress parameters and the activity of antioxidant enzymes. Lipid peroxidation levels (TBARS) were unchanged. However, CCl(4) induced oxidative damage to proteins in all tissues studied, and this injury was prevented by both extracts. Superoxide dismutase (SOD) activity was increased by CCl(4) in the cerebral cortex and decreased in other tissues. However, CCl(4) increased catalase (CAT) activity in the cerebellum and decreased it in the cerebral cortex. The SOD/CAT ratio was restored in the cerebellum by both extracts and only in the cerebral cortex by the organic extract.